Electroacupuncture for patients with diarrhea-predominant irritable bowel syndrome or functional diarrhea: A randomized controlled trial. Issue 24 (June 2016) - Zheng, Hui; Li, Ying; Zhang, Wei; Zeng, Fang; Zhou, Si-Yuan; Zheng, Hua-Bin; Zhu, Wen-Zeng; Jing, Xiang-Hong; Rong, Pei-Jing; Tang, Chun-Zhi; Wang, Fu-Chun; Liu, Zhi-Bin; et al.
Abstract : Abstract: Diarrhea-predominant irritable bowel syndrome (IBS-D) and functional diarrhea (FD) are highly prevalent, and the effectiveness of acupuncture for managing IBS-D and FD is still unknown. The aim of this study was to compare the effectiveness of electroacupuncture with loperamide. It was a prospective, randomized, parallel group controlled trial. A total of 448 participants were randomly assigned to He electroacupuncture group (n = 113), Shu-Mu electroacupuncture group (n = 111), He-Shu-Mu electroacupuncture group (n = 112), or loperamide group (n = 112). Participants in the 3 acupuncture groups received 16 sessions of electroacupuncture during a 4-week treatment phase, whereas participants in the loperamide group received oral loperamide 2 mg thrice daily. The primary outcome was the change from baseline in stool frequency at the end of the 4-weeks treatment. The secondary outcomes were the Bristol scale, the MOS 36-item short form health survey (SF-36), the weekly average number of days with normal defecations and the proportion of adverse events. Stool frequency was significantly reduced at the end of the 4-week treatment in the 4 groups (mean change from baseline, 5.35 times/week). No significant difference was found between the 3 electroacupuncture groups and the loperamide group in the primary outcome (He vs. loperamide group [mean difference 0.6, 95% CI, –1.2 to 2.4]; Shu-Mu vs. loperamide group [0.4, 95% CI, –1.4 to 2.3]; He-Shu-Mu vs. loperamide group [0.0, 95% CI, –1.8 to 1.8]). Both electroacupuncture and loperamide significantly improved the mean score of Bristol scale and increased the weekly average number of days with normal defecations and the mean scores of SF-36; they were equivalent in these outcomes. However, the participants in electroacupuncture groups did not report fewer adverse events than those in the loperamide group. Similar results were found in a subgroup analysis of separating patients with IBS-D and FD patients. Electroacupuncture is equivalent to loperamide for reducing stool frequency in IBS-D and FD patients. Further studies on cost effectiveness of acupuncture are warranted.